2008
DOI: 10.1007/s11357-008-9077-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-related atrial fibrosis

Abstract: Many age-related diseases are associated with, and may be promoted by, cardiac fibrosis. Transforming growth factor (TGF)-beta, hypoxia-induced factor (HIF), and the matrix metalloproteinase (MMP) system have been implicated in fibrogenesis. Thus, we investigated whether age is related to these systems and to atrial fibrosis. Right atrial appendages (RAA) obtained during heart surgery (n = 115) were grouped according to patients' age (<50 years, 51-60 years, 61-70 years, or >70 years). Echocardiographic ejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 53 publications
(12 reference statements)
7
39
2
1
Order By: Relevance
“…Animal studies have confirmed that atrial fibrosis with advancing age is associated with conduction slowing and arrhythmogenesis, 35,36 and human studies have demonstrated a correlation between levels of atrial fibrosis and advancing age. 37,38 By contrast, and in keeping with the present study, other studies have refuted an association between atrial fibrosis and advancing age, 39 and these findings also accord with our previous finding that human atrial CV did not directly correlate with atrial connective tissue content. 9 Among the conflicting studies correlating human atrial connective tissue, the techniques for connective tissue quantification and the age ranges of the subjects varied, but it also remains possible that in the relationship with conduction velocities what is important is not connective tissue quantification, per se, but the extent to which it causes changes in GJ coupling by altering the topology of connectivity of the myocytes.…”
Section: Advancing Age Atrial Connexins and Resistivitysupporting
confidence: 93%
See 1 more Smart Citation
“…Animal studies have confirmed that atrial fibrosis with advancing age is associated with conduction slowing and arrhythmogenesis, 35,36 and human studies have demonstrated a correlation between levels of atrial fibrosis and advancing age. 37,38 By contrast, and in keeping with the present study, other studies have refuted an association between atrial fibrosis and advancing age, 39 and these findings also accord with our previous finding that human atrial CV did not directly correlate with atrial connective tissue content. 9 Among the conflicting studies correlating human atrial connective tissue, the techniques for connective tissue quantification and the age ranges of the subjects varied, but it also remains possible that in the relationship with conduction velocities what is important is not connective tissue quantification, per se, but the extent to which it causes changes in GJ coupling by altering the topology of connectivity of the myocytes.…”
Section: Advancing Age Atrial Connexins and Resistivitysupporting
confidence: 93%
“…Animal studies have confirmed that atrial fibrosis with advancing age is associated with conduction slowing and arrhythmogenesis, 35,36 and human studies have demonstrated a correlation between levels of atrial fibrosis and advancing age. 37,38 By contrast, and in keeping with the present study, other studies have refuted an association between atrial fibrosis and advancing age, 39 and these findings also accord with our previous finding that human atrial CV did not directly correlate with atrial connective tissue content. …”
supporting
confidence: 93%
“…Atrial fibrosis is thought to promote these changes. Previously, we found atrial fibrosis to increase with the duration of AF [5] and to be associated with increasing age [6]. Once atrial fibrosis is established, it is only partly reversible and therefore contributes to sustain AF7 [7].…”
Section: Introductionmentioning
confidence: 91%
“…22 Hypertension is a possible stimulus for myocardial fibrosis. 23 TGF-␤ is an established pro-fibrotic cytokine in cardiac fibrosis [23][24][25] and is closely related to the reninangiotensin system. 26,27 Inhibition of the renin-angiotensin system (and, thus, indirectly TGF-␤) has been shown to prevent CsA-induced fibrosis.…”
Section: Allograft Myocardial Remodelingmentioning
confidence: 99%